Emissions of Methane and Nitrous Oxide from Rainfed Rice Field Treated with Different Rice Planting Systems and Nematicide Applications at Central Java, Indonesia - Wihardjaka, Anicetus; Harsanti, Elisabeth Srihayu (JOURNAL OF TROPICAL SOILS, 2015)
Rice field is issued as a source of greenhouses gases (GHGs) emissions especially methane (CH4) and nitrous oxide (N2O). Rice cultural approach could mitigate GHGs emissions i.e. through rice planting systems and nematicide application. The field experiment was conducted in rainfed rice field at Pati District, Central Java to determine effect of planting systems and nematicide application on emissions of methane and nitrous oxide from rainfed rice field. The six treatments were arranged in a randomized block design with three replicates, namely transplanted rice (TR) without applying nematicide, TR + neem cake, TR + carbofuran, direct seeded rice (DSR) without applying nematicide, DSR + neem cake, DSR + carbofuran. Parameters observed were methane flux, nitrous oxide flux, organic C content in rhizosphere, soil pH, soil redox potential surrounding rhizosphere of Ciherang variety. Methane emission under transplanted rice system was generally higher than direct seeded rice system.Â  The treatment of DSR + neem cake resulted lowest methane emission (71 kg CH4 ha-1 season-1). The TR system emitted N2O lower significantly than the DSR system. Application of nematicide inhibitor materials decreased more effectively N2O emission. The DSR system increased significantly grain yield and N uptake, while application of nematicide materials didnâ€™t increase grain yield but increased significantly N uptake. [How to Cite: Anicetus W and ES Harsanti. 2015. Emissions of Methane and Nitrous Oxide from Rainfed Rice Field Treated with Different Rice Planting Systems and Nematicide Applications at Central Java, Indonesia. J Trop Soils 20: 127-134. Doi: 10.5400/jts.2015.20.3.127]